The Effect of Bids Below 80% of the Owner Estimate on Construction Project Performance and Owner Satisfaction in Klungkung Regency - I Putu Suyoga Artha; Anak Agung Gde Agung Yana; I Nyoman Yudha Astana (International Journal Labs, 2026)
In the Klungkung Regency Government, the percentage of construction project tenders with bids below 80% of the owner estimate during the period 2021–2025 reached 34.29%. This research was conducted to analyze the effect of bids below 80% of the owner estimate on construction project performance and owner satisfaction in Klungkung Regency and to identify mitigation measures for the negative impacts of bids below 80% of the owner estimate on construction project performance and owner satisfaction. This study was carried out by distributing questionnaires to owner of construction projects procured through construction tenders conducted by the Klungkung Regency Government with bid prices below 80% of the owner estimate during the fiscal years 2021–2025. The collected data were analyzed using SEM-PLS method. The results of the SEM-PLS analysis indicate that bids below 80% of the owner estimate have a negative and significant effect on construction project performance in Klungkung Regency. Bids below 80% of the owner estimate also have a negative and significant effect on owner satisfaction. Construction project performance acts as a complementary partial mediator in the relationship. Mitigation measures include technical justification for scope changes, field verification before payment, material approval, regular site inspections, competency verification, schedule evaluation, SMK3 monitoring, BPJS membership verification, coordination meetings, and standard response times for owner instructions.